Influence of carbon and oxygen on phosphorus and aluminium co-gettering in silicon solar cells - Mahfoud, K.; Loghmarti, M.; Muller, J.C.; Siffert, P. (Materials science & engineering. B, Solid-state materials for advanced technology, 1996)
The impact of carbon and oxygen on the performance of high efficiency photovoltaic devices is still poorly understood. As oxygen is one of the dominant impurities present in silicon, various applications require different levels of oxygen to improve the device performance. In this work, we have studied the effects of the oxygen concentration in silicon on the co-diffusion of phosphorus and aluminium by rapid and conventional processes. We will compare the effectiveness of the co-diffusion of PAl in a variety of silicon materials, as a function of temperature and duration of the thermal process in a classical and a rapid thermal furnace and examine the influence of carbon and oxygen on the gettering efficiency. In particular, we will show that the large enhancement of the minority carrier diffusion length (LD) due to this process can be related to the presence of oxygen and carbon, the influence of which during the thermal cycle is of importance.